Extracts of Thai Indigenous Vegetables as Rancid Inhibitor in a Model System - Plernchai Tangkanakul; Gassinee Trakoontivakorn; Chansuda Jariyavattanavijit (Agriculture and Natural Resources, 2005)
The antioxidant property of twenty five vegetables extracted with ethanolic and water was determined by monitoring their capacities to scavenge the stable free- radicals DPPH. Oxidative rancidity in oil-in-water emulsion model was evaluated by ferric thiocyanate (FTC) method. Total phenolic content was also determined by Folin-Ciocalteu method. The ethanolic extracts were found to exhibit a higher phenolic content as well as DPPH radical scavenging activities than the water extracts. However, the data indicated that both ethanolic and water extracts had dramatically antioxidant activity determined by FTC method. Sixteen and eighteen plants of ethanolic and water extracts, respectively, performed greater rancid inhibition than synthetic antioxidant (BHA, 10 ppm). This study found no relationship between antioxidant activities through the DPPH radicals scavenging or through lipid radicals scavenging.